Annotated catalogue of South American Dalodesmidae (Diplopoda, Polydesmida) - Mesibov, Robert (Zootaxa, 2017)
All published names for genera and species of South American Dalodesmidae are presented with annotated synonymies. Semnosoma chilense (Silvestri, 1903) comb. nov. is introduced for the "orphan" species Iulidesmus chilensis Silvestri, 1903.